Anomaly-free constraints in neutrino seesaw models - Emmanuel-Costa, D.; Franco, Edison T. [UNESP]; Felipe, R. Gonzalez (Amer Physical Soc, 2009)
The implementation of seesaw mechanisms to give mass to neutrinos in the presence of an anomaly-free U(1)(X) gauge symmetry is discussed in the context of minimal extensions of the standard model. It is shown that type-I and type-III seesaw mechanisms cannot be simultaneously implemented with an anomaly-free local U(1)(X), unless the symmetry is a replica of the well-known hypercharge. For combined type-I/II or type-III/II seesaw models it is always possible to find nontrivial anomaly-free charge assignments, which are however tightly constrained, if the new neutral gauge boson is kinematically accessible at LHC. The discovery of the latter and the measurement of its decays into third-generation quarks, as well as its mixing with the standard Z boson, would allow one to discriminate among different seesaw realizations.